Reframing, Reacting, or Responding? The Climate Emergency and Higher Education in Ireland - Gibson, Andrew (Springer Nature Switzerland, 2025)
This chapter sets out the nature of Ireland’s policy response to the climate emergency as it relates to higher education, across various policy realms (national, sectoral, and institutional), and questions what these amount to in practice. Adopting a critical policy approach, it interrogates whether relevant policies merely reframe existing concerns, react to external pressures, or amount to proactive responses appropriate to the enormity of global warming. The first part of the chapter outlines government policies regarding climate change generally, and some of the unusual features of the Irish policy context, which give considerable weight to the voice of civil society. From this it moves to consider higher education policy set out by government, before addressing the institutional policy and academic research as these relate to climate change. This chapter concludes with an argument for the specific role for higher education, ‘thinking in an emergency’, and demanding transformational change.
Higher Education Policy for Tackling Climate Change
PUBLISHED
Keywords: Identities in Transformation; Smart & Sustainable Planet; CLIMATE CHANGE; CLIMATE CHANGE POLITICS; Higher Education; Higher Education Policy; Sustainability Education